CONTENT ANALYSIS OF SEVERAL PRESCHOOL PROGRAM SYSTEMS IN THE DOMAIN OF EMOTIONS – THE CASE OF BULGARIA - Gospodinova, Karina Chavdarova (PUPIL: International Journal of Teaching, Education and Learning, 2019)
Nowadays the emotional intelligence has an important place in education from early age as it is viewed as a key to future academic success and social achievements. Currently there is no existent and approved social and emotional learning curriculum in Bulgaria and the emotional education is integrated within the curriculums of the main subjects (maths, music, art, literature etc.). In this report several preschool curriculums have been investigated. The Ekman’s model of basic emotions (joy, sadness, disgust, fear, anger, surprise) is adopted in the current study and content analysis reveals the exact occurrence of words for emotions with their synonyms and derivatives. An analysis on the student’s workbooks reveals the occurrence of emotional images (human faces, faces of impersonated animals or objects, emoji’s). The results obtained are a baseline for evaluating to what extend the idea of emotions is being integrated. They suggest the need of a separate curriculum on emotions.